Beyond Religious Tolerance in Interfaith Dialogue Spaces in Yogyakarta: Reading from a Hospitality Perspective - Gerry Nelwan; Gerald Moratua Siregar (Vol. 1 No. 1 (2022): Proceeding of International Conference Cultures & Languages 2022, 2022)
Diversity in Indonesian society is part of the reality that must be interpreted as the riches or uniqueness of this nation. However, conflicts and violence continue to be issues that disturb this diverse reality. These issues have forced the campaign for religious tolerance in society to continue to be carried out. This study aims to analyze the interfaith encounters that occurred in Yogyakarta and then proceed to read it from the perspective of hospitality. This research will use a descriptive qualitative methodology with observations, literature analysis, and interviews. The focus is on the Ahmadiyya group in Yogyakarta as one of the interfaith meeting spaces. The Ahmadiyya group often opens space and provides a place for interfaith dialogue for students and young people from different religious, cultural, and belief backgrounds. The formation of a dialogue space as a form of building an attitude of tolerance is not the end of achieving harmony or peace, but establishing the dimension of hospitality is also important in this particular discourse. Especially in enrolling in the post-pandemic period, a hospitality-based meeting room is needed.